Aromatic carbohydrate amphiphile disrupts cancer spheroids and prevents relapse - Brito, Alexandra Manuela Fernandes (2020)
Spheroids recapitulate the organization, heterogeneity and microenvironment of solid tumors. Herein, we targeted spatiotemporally the accelerated metabolism of proliferative cells located on the spheroid surface that ensure structure maintenance and/or growth. We demonstrate that phosphorylated carbohydrate amphiphile acts as a potent antimetabolite due to glycolysis inhibition and to in situ formation of supramolecular net around spheroid surface where alkaline phosphatase is overexpressed. The efficiency of the treatment is higher in spheroids as compared to the conventional 2D cultures because of the 2-fold higher expression of glucose transporter 1 (GLUT1). Moreover, treated spheroids do not undergo following relapse.